Playing Chess with a Human-Scale Mobile Manipulator - Ferguson, Michael; Gero, Kim; Salles, Joao; Weis, James (Proceedings of the AAAI Conference on Artificial Intelligence, 2011)
This paper describes our efforts preparing a mobile manipulator for the 2011 AAAI Small Scale Manipulation Challenge. We describe our approach to building a low-cost mobile manipulator for human-scale environments using ROS and off-the-shelf sensory and servos.